2016
DOI: 10.1016/j.celrep.2016.11.042
|View full text |Cite
|
Sign up to set email alerts
|

TMEM258 Is a Component of the Oligosaccharyltransferase Complex Controlling ER Stress and Intestinal Inflammation

Abstract: Summary Significant insights into disease pathogenesis have been gleaned from population-level genetic studies; however, many loci associated with complex genetic disease contain numerous genes, and phenotypic associations cannot be assigned unequivocally. In particular, a gene-dense locus on chromosome 11 (61.5-61.65 Mb) has been associated with inflammatory bowel disease, rheumatoid arthritis, and coronary artery disease. Here we identify TMEM258 within this locus as a central regulator of intestinal infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…The large noncoding RNA ANRIL (antisense noncoding RNA in the INK4 locus), which is associated with cancers and metastasis, positively regulates the expression of TMEM258 ( Bochenek et al, 2013 ; Qiu et al, 2015 ). Graham et al (2016) recently reported that increased TMEM258 expression is associated with inflammatory bowel disease. Further studies should examine whether the pathology of TMEM258-associated diseases involves alterations of the LINC complex and NE architecture.…”
Section: Discussionmentioning
confidence: 99%
“…The large noncoding RNA ANRIL (antisense noncoding RNA in the INK4 locus), which is associated with cancers and metastasis, positively regulates the expression of TMEM258 ( Bochenek et al, 2013 ; Qiu et al, 2015 ). Graham et al (2016) recently reported that increased TMEM258 expression is associated with inflammatory bowel disease. Further studies should examine whether the pathology of TMEM258-associated diseases involves alterations of the LINC complex and NE architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Prdx5 was ectopically expressed in HEK293T cells as previously described (Graham et al, 2016). Briefly, cDNA constructs were cloned as PCR products into pCMV (Invitrogen) using Gibson assembly.…”
Section: Methodsmentioning
confidence: 99%
“…2a, right panel). TMEM258 catalyzes the first step in Nglycosylation of proteins in the ER and might play a role in protein translocation across the ER 29 .…”
Section: Multiple Layers Of Functional Relationships Between Proteinsmentioning
confidence: 99%